Research on the knowledge of women about the risk factors for cervical cancer - Obuchowska, Aleksandra; Wójcik, Justyna; Standyło, Arkadiusz; Ozga, Alicja; Obuchowska, Karolina; Piotrowska, Paulina (Journal of Education, Health and Sport, 2020)
Introduction: Cervical cancer (CC) is currently the eight most common cancer among women and the seventh leading cause of cancer-related death in women in Poland. Early, non-invasive cervical cancer may develop over the years without clinical symptoms. Also, given the fact that early forms are treatable effectively, it's important to get preventive examinations. It is especially important in the group of women at high risk of developing CC. Purpose: The aim of the study is to assess women's knowledge of the risk factors for cervical cancer. Material and method: Women's knowledge of cervical cancer risk factors was verified with an anonymous online questionnaire. The obtained results were analysed and checked on the basis of scientific literature. Results: The vast majority of respondents consider family history of cancer as a risk factor for CC. 75.9% of women consider infection with HPV a risk factor. Chronic vaginal infections were chosen by over half of the women. The onset of intercourse at an early age was considered a risk factor by only 24.6%, while a large number of sexual partners by 45.4%. Conclusions: The results of the conducted research indicate that the knowledge of women from the studied group about the risk factors for cervical cancer and methods of prevention is average. In order to improve the epidemiological situation of cervical cancer in Poland, efforts should be intensified to increase the education of women in this field.